2020
DOI: 10.1016/j.ebiom.2020.102727
|View full text |Cite
|
Sign up to set email alerts
|

Persistent expansion and Th1-like skewing of HIV-specific circulating T follicular helper cells during antiretroviral therapy

Abstract: Background: Untreated HIV infection leads to alterations in HIV-specific CD4 + T cells including increased expression of co-inhibitory receptors (IRs) and skewing toward a T follicular helper cell (Tfh) signature. However, which changes are maintained after suppression of viral replication with antiretroviral therapy (ART) is poorly known. Methods: We analyzed blood CD4 + T cells specific to HIV and comparative viral antigens in ART-treated people using a cytokine-independent activation-induced marker assay al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 63 publications
5
43
0
Order By: Relevance
“…Expansion of cTFH1 is well characterized following seasonal influenza immunisation, where peak frequencies in the blood correlate with both plasmablast expansion and subsequent serum neutralising antibody titres 23,30,35 . Similarly, bias toward CXCR3 + phenotypes is reported for antigen-specific cTFH in many chronic infections 36,37 . The functional significance of CXCR3 + cTFH during SARS-CoV-2 infection is currently unclear, however may reflect differences in lymph node TFH activity or egress from the GC.…”
Section: Discussionsupporting
confidence: 57%
“…Expansion of cTFH1 is well characterized following seasonal influenza immunisation, where peak frequencies in the blood correlate with both plasmablast expansion and subsequent serum neutralising antibody titres 23,30,35 . Similarly, bias toward CXCR3 + phenotypes is reported for antigen-specific cTFH in many chronic infections 36,37 . The functional significance of CXCR3 + cTFH during SARS-CoV-2 infection is currently unclear, however may reflect differences in lymph node TFH activity or egress from the GC.…”
Section: Discussionsupporting
confidence: 57%
“…11). As previously reported, KLRB1 (CD161) cells 64 , Th1 cells 25 , Th17 cells 65 , CXCR5 + cells 65,66 , and naïve cells 29 may harbor HIV-1-infected cells, although we found that naïve cells were significantly dis-enriched for HIV-1 RNA + cells ( Supplementary Fig. 11a).…”
Section: Hiv-1 Rna + Cells Have Diverse T Cell Phenotypessupporting
confidence: 80%
“…While increased cytokine release by T FH cells has been linked to IgA responses in mice ( 106 ), SIV replication has been suggested to promote accumulation of activated IL-21 producing T FH cells with skewed B cell maturation in rhesus macaques ( 107 ). Other studies have shown that SIV infection in rhesus macaques and HIV infection in humans provokes Th1 polarization of T FH cells ( 43 , 108 ) while Th1 skewed T FH cells were shown to enhance the magnitude of anti-SIV IgA responses ( 109 ). It is possible that SIV infection may have determined functional and phenotypic changes of cT FH cells in blood which could have contributed to IgA-skewed release by peripheral B cells.…”
Section: Discussionmentioning
confidence: 99%